2018
DOI: 10.3390/ijms19113572
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cardiovascular Risk Factors on Cardiac STAT3

Abstract: Nuclear, mitochondrial and cytoplasmic signal transducer and activator of transcription 3 (STAT3) regulates many cellular processes, e.g., the transcription or opening of mitochondrial permeability transition pore, and its activity depends on the phosphorylation of Tyr705 and/or Ser727 sites. In the heterogeneous network of cardiac cells, STAT3 promotes cardiac muscle differentiation, vascular element formation and extracellular matrix homeostasis. Overwhelming evidence suggests that STAT3 is beneficial for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
35
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 124 publications
(186 reference statements)
5
35
1
Order By: Relevance
“…43 Therefore, mitoSTAT3 provides cardioprotection during myocardial I/R injury. 22,[43][44][45] In the present study, knockdown or knockout of Rap1 significantly increased the expression of phosphorylated STAT3 (Ser 727 ) in response to H/R or I/R, respectively. However, whether or not Rap1 knockdown/ knockout affects mitoSTAT3 level and therefore influences on ATP synthesis, mPTP opening and ROS generation are still unclear and additional studies will be needed to dissect the specific mechanisms.…”
Section: Discussionsupporting
confidence: 54%
“…43 Therefore, mitoSTAT3 provides cardioprotection during myocardial I/R injury. 22,[43][44][45] In the present study, knockdown or knockout of Rap1 significantly increased the expression of phosphorylated STAT3 (Ser 727 ) in response to H/R or I/R, respectively. However, whether or not Rap1 knockdown/ knockout affects mitoSTAT3 level and therefore influences on ATP synthesis, mPTP opening and ROS generation are still unclear and additional studies will be needed to dissect the specific mechanisms.…”
Section: Discussionsupporting
confidence: 54%
“…In contrast, there are reports that STAT3 mediates cardioprotective activity against injury from acute and chronic stresses, such as smoking, aging, hypertension and obesity (Zouein et al 2015, Pipicz et al 2018. Several studies have also reported decreased STAT3 phosphorylation and/or activation in heart tissues of various experimental models of diabetes (Pipicz et al 2018). Therefore, the exact role of STAT3 in DCM remains an enigma.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, STAT3 has been shown to be upregulated in the tubulointerstitial compartment of renal samples from diabetic patients with progressive nephropathy (Berthier et al 2009) and in animal models of diabetic nephropathy (Matsui & Meldrum 2012). In contrast, there are reports that STAT3 mediates cardioprotective activity against injury from acute and chronic stresses, such as smoking, aging, hypertension and obesity (Zouein et al 2015, Pipicz et al 2018. Several studies have also reported decreased STAT3 phosphorylation and/or activation in heart tissues of various experimental models of diabetes (Pipicz et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This comes in addition to potential microvascular dysfunction or injury when establishing reflow. The contribution of lethal reperfusion injury to the final extent of MI has been irrefutably demonstrated in the experimental setting (Piper, Garcia-Dorado, & Ovize, 1998) and in patients with segment elevation myocardial infarction (STEMI), although here the efficacy of the therapeutic interventions has been less consistent . The time window to effectively prevent or limit myocardial injury in patients with STEMI is very short (only a few hours from the onset of chest pain), and the development of ways to reduce the myocardial consequences of ischaemia of a given severity and duration by interfering with the molecular mechanisms of ischaemic injury is a priority (Ibanez et al, 2017).…”
mentioning
confidence: 99%